User Acceptance Analysis Dana Application E-Wallet Using UTAUT 2 and UX TAM - Meliana, Putri; Mutiah, Nurul; Rahmayuda, Syahru (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2023)
DANA is a digital wallet application that has an open platform concept, meaning it can be used on different platforms but is integrated with one another. However, there were complaints that were felt by DANA application users which were conveyed in Google Playstore reviews, namely frequent errors and delays in the transaction process. This is the basis for measuring the level of acceptance of DANA application users based on the user's experience. This research model is an integration of the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model and the User Experience technology Acceptance Model (UX TAM). The data analysis technique used Partial Least Square-Structural Equation Modeling (PLS-SEM) and used SmartPLS 3 tools Data collection was carried out by randomly distributing questionnaires to 100 respondents, namely the Pontianak community with an age range of 15-40 years. Data collection was carried out by distributing questionnaires to 100 respondents, namely the Pontianak community. Of the 21 hypotheses proposed, 10 hypotheses stated there was a relationship between the two variables and the other 11 hypotheses had no relationship. The hypotheses that have an influence are Effort Expectancy on Behavior Intention, Habit on Behavior Intention, Efficiency on Effort Expectancy, Efficiency on Performance Expectancy, Output Quality on Performance Expectancy, Dependability on Habit, Stimulation on Hedonic Motivation, Output Quality on Perceived Usefulness, Dependability on Perceived Ease Of Use, and Behavioral Intention to Use Behavior. The results of the research are in the form of recommendations that are expected to improve the performance of the DANA application.